CUSTOMER PERCEPTION OF FINANCIAL INCLUSION THROUGH PRADHAN MANTRI JAN DHAN YOJANA (PMJDY) - Anto, M. Ruben; DURAIARASAN, R.M. (International Journal of Psychosocial Rehabilitation, 2020)
Inclusion in finance is the foundation of a country’s economic growth and progress. Without financial inclusion inclusive development is unlikely. The householders were not able to open the bank accounts because of financial analphabetism at present. Pradhan Mantri Jan Dhan Yojana (PMJDY) is one of India ’s excellent steps toward financial inclusion, to resolve the constraint. PMJDY’s key aims are to provide various financial services such as savings and bank accounts, remittances, loans, insurance, and pensions. There have been 31.56 million account holders currently benefiting from PMJDY. The results of the study prove that the scheme has been successful as far as Chennai is concerned.